Analysis Driving Factors of Economic Growth During Covid-19 Pandemic: Indonesian Experiences - Purba, Jan Horas Veryady (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
Pandemic Covid-19 impact on health and economic aspects. These two aspects are trade-offs with each other, so handling the health aspect also pays attention to aspects of economic growth, so that Indonesia's economic performance during the Covid-19 pandemic is well preserved. The objectives of this study were to analyze: (1) the effect of the Covid-19 pandemic and relaxation factors on public consumption, government spending, investment, and net exports; (2) the effect of public consumption, government spending, investment and net exports on Indonesia's economic growth; and (3) the factors that drive economic growth during the Covid-19 pandemic in Indonesia. The analytical method used is ordinary least square, with multiple regression. The data used are secondary data, quarterly 2018-2020 quarter. The findings of this study indicate that the Covid-19 pandemic has a negative and significant effect on public consumption, investment, exports, and imports. The relaxation factor has a positive effect on public consumption, government spending, and net exports, but has not succeeded in creating positive investment growth. Government policies seek to strengthen people's purchasing power and strengthen the production sector. This has an impact on increasing public consumption and is a dominant factor in influencing economic growth during a pandemic. The Covid-19 pandemic affected a contraction of economic growth by 2,07% and also decreased per capita income from 4.192,7 US (2019) to 3.911,7 US . The handling of Covid-19 managed to overcome the worse potential (-4,58%) and kept the per capita income from falling to 3.774,4 US . Keywords: Covid-19, economic growth, Keynesian formula, people's purchasing power